Okruchy psychoanalizy - Dybel, Paweł (Er(r)go. Teoria - Literatura - Kultura, 2008)
Paweł Dybel Crumbs of Psychoanalysis The introductory part of the text is a personal reminiscence of the author about his discovery of psychoanalysis while a young scholar forced on him unwittingly by the ossified academic institution and his unexpected fascination with the discourse he had up until then considered as a naïve 19th century naturalism. Having also analysed the intellectual climate of his academic youth (late communist Poland), which was unfavourable to his interests, the author describes the misunderstandings and bad faith which fed such an approach and, against this background, shows why outside Poland, psychoanalysis has become the inalienable part of the Western intellectual mind frame. He also discusses the way French theory “saved” psychoanalysis from pseudo-Freudian commonplaces (Horney, Fromm) by showing that the founding Freudian gesture was a denaturalization of man by means of displaying the linguistic nature of supposedly naturalistic psychoanalytic notions such as the unconscious, drive or desire, and by proposing a new anthropology of sense in which language itself, as the site in which man and consciousness are constituted, is shown to be inevitably non-coincident with itself.